Coordenação viso motora e desenvolvimento global de crianças pré-termo : avaliação e detecção de riscos no início da escolarização - Pinheiro, Raquel Cristina (2012)
The influence of preterm birth in visual-motor skills, visual perception and fine and global motor coordination has been being increasingly investigated in the initial stages of schooling. Considering the literature data that shows the relationship between prematurity and Developmental Coordination Disorder (DCD), and relations between the DCD and disorders of visual-motor integration, evaluation and research become essential in the search for possibilities of intervention in children considered at risk. By requiring motor and cognitive repertoires increasingly sophisticated, and of its importance as developmental context, the school becomes a locus for observing the behavior and performance of the child and also a context of prevention and early intervention. This study aimed to describe visual-motor coordination and global development of preterm infants at the beginning of the school and discuss the implications of performance in occupational role envisaged for this stage of its life cycle. It is a study of case-control and descriptive-correlational. The study group was composed by 18 children with a history of preterm birth that were included in the municipal school, attending preschool or first grade of elementary school, that did not have serious neurological damage. To its pairing, participants were selected - Compared Group - by sex, age, and often the same classroom. Parents / tutors provided information on child development and on the moments pre, peri and post-natal, and answered the Developmental Coordination Disorder Questionnaire-DCDQ-Brazil 2. The children were assessed using the Denver Development Screening Test II -DDST-II and the Test of Visual-Motor Integration- VMI. Descriptive analysis and statistical tests were conducted to assess the significance of the results. Such analysis revealed that the performance of preterm infants is lower when compared with the performance of full-term infants, although the difference was not significant for all items and instruments used. In DDST-II premature infants compared with children without a history of prematurity are more likely to delay in several areas of development; in DCDQ-Brazil 2 none of the children presented the classification "probably DCD", but it was possible to observe lower average score for SG; children's performance on the VMI test revealed that the premature children had lower scores in all areas. Statistical tests revealed significant differences between SG and CG for the variables Visual-Motor and Fine Motor of VMI, but significant difference between the performance of groups Adequate Weight and Low Birth Weight was observed in the variables Visual-Motor, Fine Motor and Visual Perception, all belonging to the VMI instrument, showing that weight is a more influential factor than prematurity for visual perception performance. There are significant differences in all parts of the VMI instrument when compared the groups Suspect Denver and Normal Denver and hypothesizes that the worst performance in screening tests for development can be a predictive factor for poorer performance on tests of visual-motor integration. In the groups established by variables belonging only to premature infants there was no significant difference among the groups, demonstrating that the premature child is susceptible to developmental delays independent of birth weight and gestational age. It is observed that premature infants had poorer performance on assessment instruments, and despite coping cases, prematurity represents risks to development. During the initial education, visual-motor skills and global motor coordination become more required and increasingly complex mainly due to the requirements and domains present in the process of writing and reading. Other skills are demanded at the beginning of schooling, which require the integrity of many sensorimotor systems. Difficulties in these areas can influence the performance of children in their occupational role as a student, and other occupational areas present in their life. Considering the school as a protective environment and the work of occupational therapist by collaborative consulting approach, in this context there is the potential to minimize the deficits presented by preterm children and promote their full development.